Placenta-derived mesenchymal stem cells (P-MSCs) for COVID-19 pneumonia—a regenerative dogma - Siddesh, Sushmitha Eachagattada (Stem Cell Investig, 2021)
With a robust rise in the number of COVID-19 cases, the World Health Organization (WHO) has declared COVID-19 as a pandemic on 11(th) March 2020. COVID-19 pandemic has invited global researchers from various biomedical and biotechnological researchers to plan various treatment modalities for combating this pandemic crisis. At present, there is the unavailability of specific treatment modality; however, researchers have thrown light into the exploration of mesenchymal stem cells (MSCs) to therapeutically perquisite in ameliorating immune-mediated progressive worsening in COVID-19 infected patients. Cellular therapy (CT) has revolutionized the treatment of untreatable diseases with a better clinical and functional outcome. Placenta, being considered as medical waste, contains a variety of stem cells, and hence placenta-derived MSCs (P-MSCs) owe potentiality for extrapolation to combat COVID-19 pandemic. The usage of P-MSCs in combating the COVID-19 pandemic has plausible challenges in terms of isolation, harvesting, expansion, characterization, and involvement of ethical concerns. This article provides an insight into dealing COVID-19 pandemic with P-MSCs as cell-based therapy embracing immunomodulatory and immune-privileged potentials and future prospects. Advocating prospective randomized controlled clinical trials ethically will concretely supplement for its efficacy and safety concerns.